Upholding Refugee Rights: Cessation, Transnationalism and Law’s Limitations in the Rwandan Case - Parker, Laura (African Human Mobility Review, 2021)
The cessation clause epitomises the 1951 Refugee Convention’s internal barriers to the full achievement of refugees’ rights. By examining the controversial application of this provision in the case of Rwandan refugees, this paper demonstrates the resultant infringements on refugees’ human rights, and signals a key obstacle in understanding refugee experiences: institutional insistence on subjugating refugee perspectives and knowledge. This top-heavy ‘knowing what’s best’ for refugees must cede to alternative conceptualisations of refugee rights, especially in the well-worn durable solutions debate. A rights-based approach would see transnational mobility as a solution to challenges endured by camp-based refugees in particular. The Rwandan case study is grounded in theories of today’s membership-based nation-state paradigm, and questions whether re-inscribing refugees as primary agents of their own repatriation (with or without return) can bridge the divide inherent in the exclusionary citizenship-centric logic which ultimately structures the refugee rights system, and can adequately address problems rooted in complex identity politics.